Detection of 2FAL Furanic Compound in Transformer Oil Using Optical Spectroscopy Method and Verification Using Morse Oscillation Theory - Thiviyanathan V.A.; Ker P.J.; Leong Y.S.; Jamaluddin M.Z.B.; Mun L.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Furfural; Infrared devices; Kraft paper; Power transformers; Spectroscopic analysis; Conventional methods; Fundamental theory; Near infrared region; Optical absorbance; Optical characteristics; Optical characterization; Optical spectroscopy; Oscillation theory; Oil filled transformers